2001
DOI: 10.1037/0096-3445.130.4.621
|View full text |Cite
|
Sign up to set email alerts
|

How are visuospatial working memory, executive functioning, and spatial abilities related? A latent-variable analysis.

Abstract: This study examined the relationships among visuospatial working memory (WM) executive functioning, and spatial abilities. One hundred sixty-seven participants performed visuospatial short-term memory (STM) and WM span tasks, executive functioning tasks, and a set of paper-and-pencil tests of spatial abilities that load on 3 correlated but distinguishable factors (Spatial Visualization, Spatial Relations, and Perceptual Speed). Confirmatory factor analysis results indicated that, in the visuospatial domain, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
717
9
28

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 896 publications
(809 citation statements)
references
References 53 publications
55
717
9
28
Order By: Relevance
“…Whereas verbal storage-rehearsal processes were correlated strongly with verbal reasoning and very weakly with general ability (see also Cantor et al, 1991;, spatial storage-rehearsal processes predicted both spatial reasoning and general fluid ability strongly. As we noted earlier, these findings are consistent with others demonstrating a close link between "simple" spatial storage and higher order cognitive capabilities such as executive function (Miyake et al, 2001), complex reasoning and Gf (Oberauer, in press;Shah & Miyake, 1996), and free recall of either verbal or visuospatial materials (Park et al, 2002). However, we also found that when our Gf factor was defined in a less spatially biased manner, spatial storage had a substantially weaker correlation with it.…”
Section: The Domain Specificity Of Stm Storage-rehearsal Abilities Ansupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas verbal storage-rehearsal processes were correlated strongly with verbal reasoning and very weakly with general ability (see also Cantor et al, 1991;, spatial storage-rehearsal processes predicted both spatial reasoning and general fluid ability strongly. As we noted earlier, these findings are consistent with others demonstrating a close link between "simple" spatial storage and higher order cognitive capabilities such as executive function (Miyake et al, 2001), complex reasoning and Gf (Oberauer, in press;Shah & Miyake, 1996), and free recall of either verbal or visuospatial materials (Park et al, 2002). However, we also found that when our Gf factor was defined in a less spatially biased manner, spatial storage had a substantially weaker correlation with it.…”
Section: The Domain Specificity Of Stm Storage-rehearsal Abilities Ansupporting
confidence: 92%
“…However, these spatial STM and WM tasks did not always account for the same variance in these complex cognitive measures. In the Miyake et al (2001) study, a latent-variable model with a single spatial WM-STM factor fit the data as well as one that separated the WM and STM constructs (the latter were correlated at .86), and this single spatial memory construct accounted for 35% of the variance in an executive-function construct composed of Tower of Hanoi and random generation tasks. Here, then, spatial WM and STM tasks appeared to measure a single construct related to executive attention.…”
Section: The Domain Specificity Of Stm Storage-rehearsal Abilities Anmentioning
confidence: 82%
See 1 more Smart Citation
“…Jarvis & Gathercole, 2003; Miyake et al, 2001; Shah & Miyake, 1996). Contrary to the multicomponent model (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, other competing accounts suggest that there are two independent domain‐specific components for verbal and visuospatial information, each capable of both storing and processing information (e.g. Friedman & Miyake, 2000; Jarvis & Gathercole, 2003; Miyake, Friedman, Rettinger, Shah, & Hegarty, 2001; Shah & Miyake, 1996). By these accounts, verbal WM (executive) tasks would not predict visuospatial abilities and vice versa.…”
mentioning
confidence: 99%